Differential wireless measurement technology of mount levelness of ship equipment - GE Yaming, LI Hongyuan, WANG Deqing, LIJun (Zhihui kongzhi yu fangzhen)
Levelness is an important parameter of ship mount. Aiming at the synchronous measurement of multiple mounts in mooring state, a differential wireless measurement technology of mount levelness is proposed. Using the position symmetry of the mount sensor, the measurement error caused by the non-parallelism between the measurement plane of the inclination sensor and the mount plane is eliminated. Using the combination of atomic clock and constant temperature crystal oscillator, the clock synchronization of the measurement system in the closed cabin is realized. The ship roll angle is determined by a symmetrical sensor in the transverse section of the ship, and the influence of ship deformation on the measurement results is eliminated. The experimental results show that the differential wireless measurement technology of mount levelness can realize the synchronous measurement of ship multi-mount levelness with high precision, and it has been tested and verified in the actual environment of a shipyard with good results.